The Association Between Depressive Symptoms and Insomnia in College Students in Qinghai Province: The Mediating Effect of Rumination - Xiao, Shuheng; Liu, Shuai; Zhang, Puxiao; Yu, Jia; A, Huaihong; Wu, Hui; Zhang, Fabin; Xiao, Yulan; Ma, Naiben; Zhang, Xiuqin; Ma, Xiaoxia; Li, Junfeng; et al. (Frontiers in Psychiatry, 2021)
Background: This study investigates the mediating effect of rumination on the associations between depressive symptoms and insomnia. Methods: This is a cross-sectional study. Insomnia Severity Index (ISI), Ruminant Response Scale (RRS) and Beck Depression Inventory (BDI) were determined in 12,178 college students in Qinghai province by a questionnaire network platform. Results: The prevalence of insomnia was 38.6% in the participants. Insomnia symptoms [interquartile range: 6 (3, 9)], depressive symptoms [interquartile range: 5 (1, 9)], and rumination [interquartile range: 22 (20, 26)] were positively correlated (r = 0.25–0.46, p < 0.01). Mediation effect analysis showed that the depressive symptoms affected insomnia directly and indirectly. The direct effect and the indirect effect through rumination account for 92.4 and 7.6% of the total effect, respectively. Conclusion: The study shows that insomnia, depressive symptoms, and rumination are related constructs in college students in Qinghai province. It demonstrates the direct effects and the rumination-mediated indirect effects between depressive symptoms and insomnia; the direct effects seem to be dominant.